The effect of different intensity physical activity on cardiovascular metabolic health in obese children and adolescents: An isotemporal substitution model - Cao, Youxiang; Zhu, Lin; Chen, Zekai; Zhanquan, Li; Xie, Weijun; Liang, Manna (Frontiers in Physiology, 2023)
OBJECTIVE: This study’s purpose was to investigate the effects of different intensities of physical activity on cardiovascular metabolism in obese children and adolescents based on an isochronous replacement model. METHODS: A total of 196 obese children and adolescents (mean age, 13.44 ± 1.71 years) who met the inclusion criteria and attended a summer camp from July 2019 to August 2021 were recruited for this study, and all subjects wore a GT3X+ triaxial motion accelerometer uniformly around the waist to record physical activity levels. We collected the subjects’ height, weight, and cardiovascular risk factors such as waist circumference, hip circumference, fasting lipids, blood pressure, fasting insulin, and fasting glucose before and after 4 weeks of camp and constructed cardiometabolic risk score (CMR-z). We analyzed the effects of different intensities of physical activity on cardiovascular metabolism in obese children using isotemporal substitution model (ISM). RESULTS: After 4 weeks, cardiovascular risk factors such as body weight, waist circumference, triglyceride, and total cholesterol were reduced in adolescents with obesity (P < 0.01), and CMR-z was also reduced (P < 0.01). ISM analysis revealed that all sedentary behavior (SB) replacement with 10 min of light physical activity (LPA) reduced CMR-z [β = -0.10, 95% CI (-0.20, -0.01), P = 0.04]; 10-min of moderate physical activity (MPA) replacement of SB reduced CMR-z [β = -0.32, 95% CI (-0.63, -0.01), P = 0.04]; 10-min of vigorous physical activity (VPA) replacement of SB reduced CMR-z [β = -0.39, 95% CI (-0.66, -0.12), P = 0.04]. CONCLUSION: Replacement of SB with 10 min of LPA, MPA, and VPA were all effective in improving cardiovascular risk health, respectively, but MPA or VPA was more effective.